Indicadores para la perspectiva financiera del cuadro de mando integral (CMI) en la Ronera Central - Gutiérrez López, Leidy María; Suárez González, Maylín (My University, 2019)
Esta investigación ha sido realizada en la Ronera Central “Agustín Rodríguez Mena”, con el propósito de elaborar una propuesta de indicadores para la perspectiva financiera que tribute a la construcción del Cuadro de Mando Integral (CMI) como herramienta de gestión empresarial. Para desarrollar la misma, se realizó un estudio sobre la fundamentación teórica del CMI y las perspectivas que lo conforman (Formación y Aprendizaje, Procesos, Clientes y Financiera), haciendo énfasis en esta última como objeto de estudio del presente trabajo. Para ello, se partió de la reformulación de la misión, la visión, de la selección de indicadores financieros necesarios para medir la situación actual de las finanzas en la entidad, se efectuó el análisis de los estados financieros mediante el cálculo de razones y se elaboró la matriz DAFO como herramientas que integran los indicadores seleccionados para medir los resultados económicos-financieros de la entidad.

The investment process in Cuba envisages a project aimed at alleviating the effects of the intense drought that the country has suffered in recent years, taking into account the potential here to make sea water fit for human, domestic and industrial consumption.This is part of a program aimed at ensuring the supply of water in those areas where it is complex to get through conductors, or it is very expensive to supply the vital liquid by conventional means.Taking into account the above, it is necessary to know the cost of this technology, for which the present research is proposed, whose general objective is: To expose the considerations calculating costs for seawater desalination plants by reverse osmosis. In the paper we consider the factors that affect the cost of m3 desalinated water by Reverse Osmosis in the country, considering that this technology is considered the most efficient based on its best water pressure, the feasible expansion of the Plants and their great reliability. In order to fulfill this objective, an extensive bibliographical search was made and finally conclusions are arrived at based on the research carried out.
Keywords: Cuadro de Mando Integral; Razones Financieras